Development of a new costing structure in production environment using activity based costing - Filzah Lina, Mohd Safeiee; Abu, Mohd Yazid; Nik Nurharyantie, Nik Mohd Kamil; Nurul Farahin, Zamrud (2019)
Every product should have assigns their own costing system. Traditional cost accounting (TCA) is generally used by current state of industrial area in Malaysia. There are many studies proved the weaknesses of TCA [1] and need a lot of improvements. The aim of this work is to propose a new costing system that practically capable to improve costing system in current industry practices. In this study, ABC method has been proposed to the electrics and electronics company on inductor component. There are 18 workstations involves and the data was collected based on data in 2018. As a result, an Activity-based costing (ABC) system recognized the relationship between costs, overhead activities and manufactured products, and then it can assign indirect cost to products less subjectively than traditional method.